PENGARUH LITERASI KEUANGAN DAN PERILAKU KEUANGAN TERHADAP PENDAPATAN KOPERASI KREDIT SWASTISARI DI KOTA KUPANG - Keban, Vinsensia V.L; Kellen, Pius Bumi; Tungga, Cicilia A. (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2024)
This examine ambitions to determine the impact of economic tradition and monetary conduct on the income of Kopdit Swastisari cooperative in Kupang town. This have a look at makes use of quantitative strategies, in particular information evaluation, to process respondent survey information. To decide the pattern with the aid of easy random sampling and the pattern used on this study, 50 contributors of Swastisari cooperative in Kupang town had been the primary records. statistics have been collected the use of questionnaires disbursed to participants of the cooperative. The facts analysis techniques used on this study are more than one linear regression analysis, T-take a look at and F-test. The results of this look at display that financial culture and financial conduct have a substantial have an impact on on the earnings of Kopdit Swastisari cooperative in Kupang city. The hints on this take a look at are intended to assist individuals of the Kopdit Swastisari Cooperative in Kupang metropolis to higher apprehend price range and behavior further studies to allow extra signs and variables.   Keywords: Financial knowledge, financial behavior, income.